Fire hazards at housing projects in Malaysia: A legal overview (Part 1) - Md Dahlan, Nuarrual Hilal (2021)
Fire hazards at housing projects is one of the housing catastrophes in Malaysia. Some of the reasons leading to occurrences of fire are failure of the developers to construct building using approved materials, negligence of the house occupants in using electricity which sparks fires and causes electrical hazards, electrical failure or malfunction, unattended cooking, heating equipment hazards, smoking materials, candle materials, and heat sources too close to combustibles. The catastrophe has resulted in pecuniary and non-pecuniary losses, deaths and injuries to the purchaser residents. Fire hazard is one of the critical matters that developers must address during the development building stage. The developer should get views and approvals from relevant technical agencies, for instance, the Department of Fire and Rescue (Jabatan Bomba & Penyelamat). This paper aims to describe and study fire hazard legal issues and law relating to fire hazards in housing projects. This paper uses legal research methodology and qualitative research methodology, particularly concerning eliciting information through interviews with relevant parties to study the problem. The writing consists of 2 parts. The instant paper is the Part 1 discussing the issues and legal requirements by the Department of Fire and Rescue before Certificate of Completion and Compliance (CCC) can be issued. This paper finds that there are issues that have caused fire hazards in housing projects. This paper, it is submitted, can add to enrich the fire hazard legal literature and discussion on the current policy on fire safety in housing projects, particularly the housing development guidelines and the current National Housing Policy (DPN) (2018-2025).